Extended human papillomavirus genotype distribution in cervical intraepithelial neoplasia and cancer: Analysis of 40 352 cases from a large academic gynecologic center in China. Issue 1 (21st November 2022) - Tang, Xiao; Jones, Terri E.; Jiang, Wei; Austin, Marshall; He, Yanmei; Li, Lei; Tong, Lingling; Wang, Cheng; Yang, Kaixuan; Yin, Rutie; Zhao, Chengquan
Abstract: Our aim was to conduct a large epidemiologic analysis of the distribution of human papilloma virus (HPV) genotypes associated with cervical neoplasias and cancers at a major Chinese gynecologic center. The pathologic database was searched for cervical histopathologic diagnoses with prior HPV genotyping from liquid cervical cytology specimens obtained ≤6 months before biopsy. HPV testing was performed by using the Tellgenplex HPV27 or YanengBio HPV23 genotyping assays. A total of 40 352 cases meeting study criteria were identified. High risk human papillomavirus (hrHPV) was detected in 94.1% of squamous cancers compared to in only 83.3% of cervical adenocarcinomas. The prevalence of multiple HPV infections was highest in cervical intraepithelial neoplasia 1 (CIN1) (33.8%) and decreased with increasing severity of squamous lesions. The distribution of HPV genotypes was similar between CIN1 and histopathologic‐negative cases. HPV16 was one of the three most common hrHPV genotypes before all histopathologic abnormalities, ranging from 72.0% for cervical cancers, 38.7% for CIN2/3/AIS, 13.1% for CIN1, and 9.1% for biopsy‐negative cases. HPV16 and HPV18 accounted for over 87.2% of detected hrHPV genotypes for all glandular intraepithelial neoplastic lesions and cancers, whereas squamous lesions did not show this pattern. 80.3% of cervical cancers were associated with genotypes covered by HPV16/18 vaccines and 89.6% with genotypes covered by 9‐valent vaccination.